Why Jane Austen? - Brownstein, Rachel M (Columbia University Press, 2011)
Ebook from IG Library; Includes bibliographical references and indexes; Introduction: Knowing theory -- Pt. 1. Theories of textuality -- The death of the author -- Structure, sign, and play -- Pt. 2. Psychological theories -- The mirror stage -- Women's time -- Pt. 3. Theories of society -- Systems of constraint -- Simulacra and simulation -- Lines of flight -- Conclusion: Talking back to theory; From the first publication of Pride and Prejudice to recent film versions of her life and work, Jane Austen has continued to provoke controversy and inspire fantasies of peculiar intimacy. Whether celebrated for her realism, proto-feminism, or patrician gentility, imagined as a subversive or a political conservative, Austen generates passions shaped by the ideologies and trends of her readers' timeand by her own memorable stories, characters, and elusive narrative cool